Methods for Cervical Cancer Screening - Vargas-Revilla, Tatiana (2014)
Cervical cancer affects a great portion of the world’s female population,and it became the third cause of death for women in developing countries such as CostaRica.The most common method to diagnose this cancer is the Papanicolaou testor Papsmear; nevertheless, high levels of sensitivity and specificity are required. Consequently, different organizations have developed multiple methods to detect and classify this cancer. This article is divided in three sections: the first one focuses on the general impact of cervical cancer has hadin CostaRica, these condsection gathers information about different methodologies used around the world to detect this cancer and the third one makes reference to the current development of the screening devise in Mexico that works as a monitoring system and can used by women without external assistance.